GENDER DI SEPUTAR PERGELARAN WAYANG JEKDONG DALAM BUDAYA JAWA TIMURAN - Wisma Nugraha Christianto (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2009)
Using an ethnographic research technique, within aninterpretive framework, this study sought to understand genderrelations in some wayang Jekdong performances from the perspectiveof the members themselves. Using interviews and observation, theresearch was carried out continuously over a period several months.Having developed categories and established themes, the data wereinterpreted using the analytic narrative. The entry of women into thefields of wayang Jekdong performances has affected gender roles anddivision of labor within households. Men argue that, while manywomen can try to